2017
DOI: 10.2134/jeq2016.07.0272
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of the APEX Model to Simulate Management Practice Effects on Runoff, Sediment, and Phosphorus Loss

Abstract: Process-based computer models have been proposed as a tool to generate data for Phosphorus (P) Index assessment and development. Although models are commonly used to simulate P loss from agriculture using managements that are different from the calibration data, this use of models has not been fully tested. The objective of this study is to determine if the Agricultural Policy Environmental eXtender (APEX) model can accurately simulate runoff, sediment, total P, and dissolved P loss from 0.4 to 1.5 ha of agric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…Better understanding of how management practices affect these parameters is desirable for more accuracy in the estimation of practice effectiveness. Bhandari et al (2017) arrived at a similar conclusion and recommended using calibration data that cover both practice and no-practice scenarios.…”
Section: Cross-validation Of Nb and Ub Modelsmentioning
confidence: 73%
See 1 more Smart Citation
“…Better understanding of how management practices affect these parameters is desirable for more accuracy in the estimation of practice effectiveness. Bhandari et al (2017) arrived at a similar conclusion and recommended using calibration data that cover both practice and no-practice scenarios.…”
Section: Cross-validation Of Nb and Ub Modelsmentioning
confidence: 73%
“…The 23% and 30% reductions in runoff and TP, respectively, in the agroforestry watershed based on all March-November simulated daily values (table 8) were close to the total effect with the UB model (25% and 28%, respectively; table 7). On the other hand, the reductions estimated with the NB model (not shown) were farther apart (30% and 39%, respectively), which emphasizes the need for a model that performs well with and without the practice being evaluated (Bhandari et al, 2017). Discharge measurement methods with a flow-control structure but without periodic discharge checks typically yield measurement errors of 5% to 10% (Harmel et al, 2006).…”
Section: Buffer Effectiveness Using Simulated Paired Watershed Approachmentioning
confidence: 96%
“…Calibration resulted in a reduced range of values for each indicator, as indicated by a smaller standard deviation, and increased the number of sites where PEC were met. Sites for which sediment r 2 and NSE did not meet the PEC were characterized by small sediment loads (average annualized load < 0.8 Mg ha −1 ; Bhandari et al, 2017; Nelson et al, 2017). …”
Section: Resultsmentioning
confidence: 99%
“…It potentially could be used to evaluate the runoff component of these indices, provided it is successfully tested on soils with different characteristics. Other papers in this special section include analyses of the calibrated parameterizations within and beyond the calibration conditions (Bhandari et al, 2017) and development of a regional parameterization that could provide acceptable performance (Nelson et al, 2017). …”
Section: Resultsmentioning
confidence: 99%
“…Baffaut et al (2017) found that an uncalibrated Agricultural Policy Environmental eXtender (APEX) model failed to adequately simulate edge‐of‐field P loss. However, it was found that, with calibration, the APEX model could simulate P loss resulting from different management practices at nearby locations with similar soils (Senaviratne et al, unpublished data, 2016; Bhandari et al, 2017). If APEX could be calibrated at a regional level, then it could be used to generate the required P‐loss estimates for P Index evaluation.…”
mentioning
confidence: 99%